O Apego ao Pet e a Cultura de Consumo: uma abordagem pelo Budismo Mādhyāmaka - SAKUMA, Regina Harumi (2022)
This research aims to investigate, from a Buddhist Mādhyāmaka school´s perspective, how attachment (upādāna) manifests itself in relationships with pets and what are the consequences in the private and social spheres in our current society of consumption. In this sense, we seek to analyze the relationships in which the pet takes over the role of both consumer – under the status of family member – and consumed – as animal-product. The research attempts to correlate this phenomenon with concepts presented by the Mādhyāmaka school about the construction of the attachment (upādāna). The choice of Mādhyāmaka thought is due to its foundation in important concepts about the processes of production of attachment, which is a valuable tool of analysis to be used in our understanding of what guides the individual within the contemporary society of consumption. The over superimposition or projection (samāropa) of the self into things – people, animals, or objects – as a form of attachment (upādāna) is posited to bring more estrangement from reality as it really is, generating the false notion of a separate, autonomous, and independent individual. Consequently, their actions are not seen under their multidimensional aspect of relational or interdependent cause structure, resulting in deleterious impacts on all relational constructions – between themselves and with pets. (AU)